Effect of compatibilizer and coupling agent on properties of recycled high density polyethylene/ ethylene vinyl acetate / eggshell powder composites - Nur Farahana Ramli (School of Materials Engineering, 2016)
This study was conducted to investigate the effect of compatibilizers and coupling agent on the properties of rHDPE/EVA/ESP composites. The filler loading was varied from 0, 5, 15, 20 and 25 phr loading. Meanwhile, the ratio of the rHDPE/EVA matrix composition was 50/50 phr is to observe the effect of both dispersed and continuous blend of rHDPE and EVA phases. The compounding of the composites was carried out by melt blending in Brabender Plasticorder internal mixer at 160 C with rotor speed of 50 rpm for 10 minutes.